Telemedicine Networks of EHAS Foundation in Latin America - Prieto-Egido, Ignacio; Simó-Reigadas, Javier; Liñán-Benítez, Leopoldo; García-Giganto, Víctor; Martínez-Fernández, Andrés (Frontiers in Public Health, 2014)
Rural areas in developing countries are characterized by lack of resources, low population density and scarcity of communications infrastructure. These circumstances make it difficult to provide appropriate healthcare services. This paper explains research results achieved by EHAS (Enlace Hispano Americano de Salud - Hispano American Health Link) and how they have contributed to improve healthcare in isolated areas of developing countries through the use of Information and Communication Technologies (ICT). As the first step, EHAS always collaborates with public health systems to identify its communication and information needs. Based on the analysis of needs, EHAS does research on appropriate technologies to provide communication in each context and on information systems suited to needs of health personnel. In parallel, EHAS has worked to provide applications that, making use of the communications services installed, could improve the healthcare services in these remote areas. In this line, solutions to improve epidemiological surveillance or to provide telemedicine services (like a digital stethoscope or a tele-microscopy system) have been developed. EHAS has also performed several researches trying to ensure the sustainability of their solutions and has summarized them in a Management Framework for Sustainable e-Healthcare Provision. Finally, the effort to spread acquired knowledge has crystallized in a book that details all the technologies and procedures previously mentioned.